Screen memories. - Iida, Takayo (Mito : Contemporary Art Center Art Tower Mito, 2002)
Aitken, Doug ; Anger, Kenneth ; Breitz, Candice ; Demand, Thomas ; Evans, Cerith Wyn ; Gonzalez-Foerster, Dominique ; Ikeda, Ken ; Julien, Isaac ; Kentridge, William ; Korine, Harmony ; Schorr, Collier ; Sugimoto Hiroshi ; Tanaka, Koki ; Waters, John ; Wilson, Jane & Louise ; Yokoo, Tadanori
ind. tent., gr. tent. p. 74-81
Engels & Japans
Screen memories, Contemporary Art Center Art Tower Mito, Mito-shi, April 13 - June 9, 2002
boek